Die Bedeutung von Innovation und Diffusion neuer Technologien für die Regionalpolitik - Giese, Ernst; Nipper, Josef (ERDKUNDE, 1984)
Regional policy in the Federal Republic of Germany has, above all, formerly concerned itself with the assumption of a high regional mobility of firms and capital. Attempts have been made with the help of regional development measures to direct this mobility readiness towards structurally weak, underdeveloped marginal areas of the Federal Republic of Germany. These attempts were still showing signs of success up to the beginning of the 70s, so that the results of earlier efficiency analyses as well as the development of the international division of labour led to the conclusion that a change in regional policy is essential in order to strengthen the competitiveness of the development areas so that a more comprehensive estimation than before will have to be established. This aims at using the capacity of the region to achieve its optimal development, especially for the strengthening of each area of production, and aims at the manufacture of what were originally called intelligent products and aims at the development of new technologies. Knowledge of requirements, influencing factors and the consequences of innovation and diffusion processes is an essential basis for an adequate regional policy. In the Federal Republic of Germany, therefore, large numbers of regional policy makers are calling for a strategically new orientation of regional policy in the direction of a stronger, innovation - orientated regional policy. Before carrying out the new regional policy, however, the question should be raised whether its basis is theoretically and above all empirically secured. This will be done in the investigation based upon the results to hand of innovation and diffusion research into technological innovations.